2022
DOI: 10.3390/biom12030389
|View full text |Cite
|
Sign up to set email alerts
|

Desmopressin Stimulates Nitric Oxide Production in Human Lung Microvascular Endothelial Cells

Abstract: Desmopressin (dDAVP) is the best characterized analogue of vasopressin, the endocrine regulator of water balance endowed with potent vasoconstrictive effects. Despite the use of dDAVP in clinical practice, ranging from the treatment of nephrogenic diabetes insipidus to bleeding disorders, much remains to be understood about the impact of the drug on endothelial phenotype. The aim of this study was, thus, to evaluate the effects of desmopressin on the viability and function of human pulmonary microvascular endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…31,32 Even more importantly, studies conducted in animals have shown that nitric oxide modulates water and electrolyte handling along nephron partly via non-cGMPdependent mechanisms, 34 and decreases AVP-stimulated water and sodium reabsorption in the collecting duct. 35 It is also noteworthy to mention that in rats exposed to a continuous intravascular infusion of l-deamino-8-arginine-vasopressin, 36 which may increase nitric oxide formation, 37 plasma volume expansion was accompanied by a progressive increase in urine flow and decreases in urine osmolality and free water reabsorption despite the presence of AVP, 36 a phenomenon known as renal "escape". 38,39 Taken together, these data suggest that the process of escape from AVP-induced antidiuresis might have occurred in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Even more importantly, studies conducted in animals have shown that nitric oxide modulates water and electrolyte handling along nephron partly via non-cGMPdependent mechanisms, 34 and decreases AVP-stimulated water and sodium reabsorption in the collecting duct. 35 It is also noteworthy to mention that in rats exposed to a continuous intravascular infusion of l-deamino-8-arginine-vasopressin, 36 which may increase nitric oxide formation, 37 plasma volume expansion was accompanied by a progressive increase in urine flow and decreases in urine osmolality and free water reabsorption despite the presence of AVP, 36 a phenomenon known as renal "escape". 38,39 Taken together, these data suggest that the process of escape from AVP-induced antidiuresis might have occurred in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…The production of nitric oxide (NO) was determined by means of a fluorimetric approach, addressing the production of the fluorescent molecule 1-(H)-naphtotriazole from 2,3-diaminonaphthalene (DAN) in an acid environment, as previously described [32]. In total, 100 µL of the cell medium was mixed with 20 µL of DAN (0.025 mg/mL in 0.31 M HCl).…”
Section: Determination Of Nitric Oxide Productionmentioning
confidence: 99%